The characterization and evaluation of the foreign policy of President Donald Trump - Namihas, Sandra (2021)
US foreign policy during the Donald Trump administration had very unique characteristics both in its forms and mechanisms of communication, as well as in its design and execution. Broadly speaking, it can be noted that this policy was distinguished by the securitization of issues, a mercantilist vision of trade, directed protectionism, relative isolationism, a low commitment to international cooperation and a setback in the values that traditionally promoted the superpower.